New development: Blockchain—a revolutionary tool for the public sector. Issue 5 (4th July 2021) - Yfantis, Vasileios; Leligou, Helen C.; Ntalianis, Klimis
ABSTRACT: This article discusses the concept of blockchain and its application to public administration research as a tool to increase trust in the government. The contribution of this article is that it unveils the advantages and disadvantages of blockchain so that both decision-makers (who intend to adopt this innovative technology to increase the transparency of the transactions in the public sector) and users (citizens and public servants) are well informed and prepared.